1985
DOI: 10.1002/cne.902310106
|View full text |Cite
|
Sign up to set email alerts
|

The somatotopic organization of primary afferent terminals in the superficial laminae of the dorsal horn of the rat spinal cord

Abstract: Transganglionic transport of wheatgerm agglutinin conjugated horse-radish peroxidase (WGA-HRP) was used to reveal the central distribution of terminals of primary afferent fibers from peripheral nerves innervating the hind leg of the rat. In separate experiments the sizes and locations of cutaneous peripheral receptive fields were determined by electrophysiological recording techniques for each of the nerves that had been labeled with WGA-HRP. By using digital image analysis, the sizes and positions of the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
185
2
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 433 publications
(217 citation statements)
references
References 54 publications
29
185
2
1
Order By: Relevance
“…Most labelled neurons evoked by the tumour graft were detected ipsilaterally at the L3-L5 levels, consistent with the somatotopic organization of the primary afferent fibres that innervate the grafted hind limb (Molander et al, 1984;Swett and Woolf, 1985). Because spinal Fos expression reflects neuronal activity (Hunt et al, 1987;Morgan et al, 1987), the present observations demonstrate the existence of a primary afferent transmission from the peripheral tumour and/or the adjacent tissues to the spinal cord.…”
Section: Discussionsupporting
confidence: 81%
“…Most labelled neurons evoked by the tumour graft were detected ipsilaterally at the L3-L5 levels, consistent with the somatotopic organization of the primary afferent fibres that innervate the grafted hind limb (Molander et al, 1984;Swett and Woolf, 1985). Because spinal Fos expression reflects neuronal activity (Hunt et al, 1987;Morgan et al, 1987), the present observations demonstrate the existence of a primary afferent transmission from the peripheral tumour and/or the adjacent tissues to the spinal cord.…”
Section: Discussionsupporting
confidence: 81%
“…Substance P labeling has been found to be intense in lamina IIo, suggesting that peptidergic PAFs make considerable synaptic input to this sublamina (Doly et al, 2004). In addition, some studies have shown that lamina IIi is prominently labeled by isolectin-B4 (IB4), an ␣-D-galactose-binding lectin from Griffonia (Bandeiraea) simplicifolia that preferentially labels nonpeptidergic fine-caliber PAFs (Swett and Woolf, 1985;Silverman and Kruger, 1988a,b;Molliver et al, 1997;Bennett et al, 1998). Other groups, however, have shown termination of IB4-reactive fibers in both laminas IIo and IIi (Wang et al, 1994), whereas a relatively recent transganglionic labeling study demonstrated prominent labeling of mouse lamina IIo with IB4 (Woodbury et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a small but distinct spread of microglia into the intact sural territory of the dorsal horn in L4/5 which can be clearly seen in the lower panel where the CTB and IB4 labelling (left) have been separated from the microglial labeling (right). However, the characteristic 'saphenous notch' (the gap in CTB labelling in L3 in both naïve and SNI where the adjacent saphenous nerve central terminals project) (Swett and Woolf, 1985) is also present in the microglial labeling in the SNI example. Therefore, there is a spread of microglial activity outside the injured central terminal fields following SNI, but it is restricted to the central terminals of the intact branch of the sciatic nerve.…”
Section: Stereological Counting Of Microglia In the Dorsal Hornmentioning
confidence: 99%
“…The central projections of peripheral sensory nerves to lamina II of the dorsal horn are somatotopically arranged (Swett and Woolf, 1985;Molander and Grant, 1986;Woolf and Fitzgerald, 1986;Shortland et al, 1989) (Fig. 5).…”
Section: Somatotopymentioning
confidence: 99%